My Fault? Coworker Incivility and Organizational Citizenship Behavior: The Moderating Role of Attribution Orientation on State Guilt - Wang, Qiong; Teng, Xiaofei; Cai, Zijun; Qu, Yi; Qian, Jing (Frontiers in Psychology, 2021)
The effect of workplace incivility on individuals’ behavior has been widely concerned in recent years. Previous research has largely linked uncivilized workplaces to discrete emotions such as anger and frustration, as well as negative behaviors such as withdrawal and aggression. However, little research has focused on the specific role of introverted discrete emotions (i.e., guilt). At the same time, the role of individual differences (i.e., attribution orientation) has not been paid enough attention. Based on attribution theory, the current study examines how coworker incivility influences individuals’ organizational citizenship behavior (OCB), and the moderating role of internal attribution orientation on this process. Using 109 employees' data for 10 consecutive working days as samples, we employed the PROCESS macro and MPLUS to examine our hypotheses. The results indicated that coworker incivility experience was positively related to employees’ state guilt only when they were high in internal attribution orientation rather than low. State guilt, in turn, was positively related to their organization citizenship behavior. This study expands the research of emotional response to uncivilized experience and provides a new perspective to understand the relationship between workplace incivility and potential positive outcomes. The implications of the general findings are discussed.